"It's because it's cancer, not because you're a Traveller"-exploring lay understanding of cancer in English Romany Gypsy and Irish Traveller communities. (June 2018) - Berlin, Jenni; Smith, David; Newton, Paul
Abstract: Purpose: The lay understanding of cancer among English Romany Gypsies and Irish Travellers, has not been studied in depth before. Lay understandings of cancer, and illness in general, varies between different ethnic groups suggesting that procedures that work for one community may not work for another. Therefore, the measures that are in place in the UK to educate and treat people with cancer may not work for the - often hard to reach - Gypsy and Traveller communities. This study explores Gypsies and Travellers lay perceptions of cancer. Method: In collaboration with community interviewers, 18 Gypsies and Travellers were recruited to take part in this study. Data comes from four semi-structured focus groups that were transcribed and thematically analysed using data-driven coding. Results: A lack of trust of the wider society has contributed to some Gypsies and Travellers' health related practices as has the persistence of old customs that negatively influence their health. As a reticence towards seeking outside help often exists, information about cancer is sought from family members. When engaged with cancer services however, Gypsies and Travellers generally feel them to be non-discriminative. Conclusions: Health professionals need to develop a better understanding of Gypsy and Travellers' health beliefs and practices in order to successfully interact with them. Information about cancer has to be delivered in an understandable form and to places where it reaches these communities. Because of historical societal discrimination, including by some health services, engaging with Gypsies and Travellers may require considerably more time and effort. Highlights: The lack of trust of outside society negatively influences Gypsies and Travellers' health. Visiting traditional 'curing men' is a part of Irish Travellers' health behaviour. Information about cancer is first sought from family members, even if this information has proven to be inaccurate in the past. Gypsies' and Travellers' gender rules and restrictions cause conflicts with health professionals. Gypsies and Travellers find cancer services to be the least discriminative, compared to other health services.